You are on page 1of 5

IN T E G R A T IO N FO R M U LA S T his page contains a list of com m only used integration form ulas.

A pplications of each form ula can be found on the page that follow s. 1.

x r dx =

x r +1 +c r +1

1 A . kdx = kx + c w here k is a constant 2.

f ( x ) dx = k f ( x ) dx

w here k is the constant 3. 4. 5. 6. 7.

[ f ( x ) + g(x) ] dx = f ( x ) dx + g (x) dx e d x = e + c e f '( x ) d x =e + c


x x f(x) f(x)

d x = l nx + c

f '( x ) dx = ln f(x) + c f (x) 8. Integration by S ubstitution

f (u) d u = F (u) + c
w here u = g (x) and du = g' (x) dx 9. Integration by P arts

f (x) g'( x)dx = f(x)g(x ) - f ' (x)g(x)dx 10. ccs x dx =sin f (x) + c 11. [ cos f (x) ] f (x)dx = sin f(x) + c 12. sin x dx = - cos x + c 13. [ sin f(x) ] f '( x)dx = cos f (x) + c 14. sec xdx = tan x + c 15. [ sec f (x) ]f (x)d x= tan f(x) + c
' 2 2 1

xr+1 1. x dx = +C r+1
r

x8 Ex. x dx = +C 8
7

1A. kdx =kx + C where k is a constant 2.

Ex.

5 dx = 5x + C
6 5x dx = 5 x dx 6

kf (x) = k F (x) dx

Ex.

where k is a constant 3. [f(x) + g (x) +dx = f(x)dx + g (x) dx

5x7 +C 7

Ex.

(2x + 3x + 2)dx = 2x dx + 3xdx + 2dx =


2 2

2x3 3x2 + + 2x + C 3 2 4. ex dx = ex + C 5. Ex.

6e dx = 6 e dx
x x

=6ex + C

f(x)

f '(x)dx = ef(x) + C

Ex. Ex.

e e

2x2 +1

4xdx = e2x +1 + C
2

6.

x +C x dx = ln

1 dx = e3x 3dx 3 1 3x = e 3dx 3 33x = +C 3 Note: This problem can also be worked using the integration by substitution method (see #8). 5dx dx Ex. = 5 x x
3x

= 5 ln x +C 7.

f (x)

f ' (x)

+ C dx = ln f(x)

Ex.

2x dx = ln x2 + 1 + C 2 +1

1 (3x 2 + 3) 3 Ex. x 3 + 3x + 2 dx 1 3x 2 + 3 dx = x 2 + 3x + 2 3 1 = ln x 3 + 3x + 2 + C 3 N ote: T his problem can also be w orked using the integration by substitution m ethod (see #8) . x2 +1 dx = x 3 + 3x + 2 Ex. 8.Integration by Substitution

(x

+ 3) 4 2 xdx

u=x 2 + 3 du=2xdx

f(u)du = F(u) + C
w here u = g(x) and du=g ' (x)dx

(x

+ 3) 4 2 xdx = u 4 du u5 +C 5 (x 2 + 3) 5 = +C 5 =

Also w ritten as:

f(g(x))g ' (x) dx = F(g)(x) + C


Ex.

x 3 + 1 dx u = x3 +1

du =3x 2 dx

x 3 + 1 dx = =

x 3 + 1 3x 2 dx

1 c 3 + 1 3x 2 dx 3 1 = u du 3 1 1 = u 2 du 3
3

1 u2 = +C 3 3 2 2 3 = u2 +C 9 3 2 = ( x 3 + 1) 2 + C 9 2 = ( x 3 + 1) 3 + C 9

9. Integration by Parts

Ex.

ln x dx g(x) = x G(x) = x3 3

f (x) g ' (x) = f(x)g(x) - f ' (x)g(x)dx

f(x) = ln x f '(x) = 1 x

Also written as:

2 x ln x dx =ln x

udv = uv - vdu where


u = f (x) dv = g(x)dx du = f ' (x) dx v =G(x)

x3 3 x3 = 3 =

x3 1 x3 dx 3 x 3 2 1 ln x - x dx 3 x3 ln x +C 9

10.

cos x dx = sin x + C

Ex.

cos x dx 1 = cos x dx 2 2 sin x = +C 2 1

11. [cos f(x)] f ' (x) dx = sin f (x) + C

Ex.

cos 4x dx = 4 cos 4x 4dx


=

1 cos 4x 4dx 4 1 = sin 4x 4 Note: This problem can also be worked using the integration by substitution method (see #8). 12. sin x dx = -cos x + C 13. [sin f(x)]f '(x) dx = -cos f (x) + C Ex.

-2 sin x dx = -2 sin x dx
= -2(-cos x) + C = 2 cos x + C

Ex. x sin(x 2 + 1)dx = =

2[sin(x

+1)]2xdx

14. sec2 x dx = tan x + C

1 [sin(x 2 + 1) + 2xdx 2 1 = - cos(x 2 + 1) + C 2 Note: This problem can also be worked by the integration by substitution method (see #8). Ex.

9 sec x dx = 9 sec x dx
2 2

= 9 tan x + C

15. [sec 2 f(x)] f '(x) dx = tan f(x) + C

Ex.

2x
2

sec2 (x 3 + 1)dx =
2 3

3 [sec (x

+ 1)] 3x 2 dx =

2 [sec 2 (x 3 + 1)]3x 2dx = 3 2 tan(x 3 + 1) + C 3 Note: This problem can also be worked by the integration by substitution method (see #8).